Spontaneous formation of Cu2O–g-C3N4 core–shell nanowires for photocurrent and humidity responses1. Issue 21 (7th June 2015) - Wang, Lixia; Zhao, Fei; Han, Qing; Hu, Chuangang; Lv, Lingxiao; Chen, Nan; Qu, Liangti
<x xml:space="preserve">Abstract</x> Rationally designed one-dimensional Cu2O–g-C3N4 core–shell nanowires have been prepared by a spontaneous reduction and assembly process, which possesses the moisture sensitivity and photocurrent response.